Quantitative Analysis of Simvastatin and Ezetimibe of Drugs in Combined Dosage Forms by HPLC - B.STEPHEN RATHINARAJ; S.VIJAYA KUMAR; S.SUDHARSHINI; B.THIRUPATHY; GURUSHARAN (International Journal of Pharma and Bio Sciences, 2010)
A high performance liquid chromatographic method was developed for the quantitative analysis of drugs in a combined dosage form. The separation was effected on a phenomenex C18 column (250mm x 4.6mm i.d. particle size 5µ) using mobile phase consisting of 1M ammonium acetate buffer and acetonitrile (55: 45 v/v) at a flow rate 1.8mL/min. The detection was made at 230nm the retention times for ezetimibe and simvastatin were 4.5 and 20.1 min respectively. Calibration curves were linear over the ranges of 10-50µg/mL for ezetimibe and simvastatin. The proposed method was validated as per the ICH and USP guidelines. The method is accurate, precise and found to be suitable for the quantitative analysis of drugs in a combined dosage form.